Improving the contribution of livestock to crop-animal systems in rainfed areas in Southeast Asia: Proceedings of a workshop - Devendra, C.; Frio, A. (International Livestock Research Institute, 2000)
The second workshop of the Crop-Animal Systems Research Network (CASREN) project embodies continuing activities on increasing the contribution of livestock to improving productivity of crop-animal systems in Southeast Asia. This workshop report involves four sessions. Session one focusses on ecoregional research on crop-animal systems and provides background information relevant to the project. This includes presentations on crop-animal research perspectives, policy options for the livestock sector, GIS application for site characterisation and definition of research domains; methodologies to address all year round feeding systems, ex-ante analyses for technical options, and methodologies for data analysis. Session two is devoted to presentations on the results of the household surveys, and based on these, session three discusses the proposed interventions by individual countries. The latter two sessions involves considerable discussion in ensuring the relevance and implementation of the proposed interventions.